Efecto de la infusión de la flor de Jamaica sobre los parámetros productivos y características organolépticas de la carne de pollos Cobb 500 - Olivo Rizo, Tahina Nayelhi (2025)
This experimental research was carried out with the objective of evaluating the effect of the Jamaican flower as an infusion in the water of Cobb 500 chickens, the research was developed in a poultry production located in the San José Compound of the Baba Canton belonging to the province of Los Ríos, 100 chickens of the Cobb 500 line were used that were distributed in 3 treatments and a control, each treatment had 5 repetitions and each repetition was made up of 5 animal units, the impact that the Jamaican Flower had on the productive parameters (feed conversion, weight gain, feed consumption, etc.) in chickens and the organoleptic characteristics of the meat (smell, flavor, color, texture, etc.) was evaluated. It is worth mentioning that the Jamaican flower has been used for many years as a natural medicine by humans since it has beneficial properties for health such as anti-inflammatory of the body, controlling blood fat levels, fighting diabetes, among others. The experimental design used in this research for statistical analysis was the Completely Randomized Design, the collected data were evaluated through the Infostat statistical software and the Tukey test at 5%. The results obtained were the following: average weight gain per bird: T0: 2862.00 grams; T1: 2792.80 grams; T2: 2755.40 grams; T3: 2899.40 grams. In the average feed consumption variable per treatment: T0: 21900.00 grams; T1: 2091.00 grams; T2: 21590.00 grams; T3: 22000.00 grams. In the feed conversion variable by treatments was: T0: 1.52 grams; T1: 1.51 grams; T2: 1.55 grams; T3: 1.52 grams. For the variable of water consumption with hibiscus infusion by treatment, the results were: T0: 0 ml; T1: 10,441.67 ml; T2: 10,033.33 ml; T3: 9,683.33 ml. The mortality variable was 3%. The benefit-cost ratios were as follows: T0: 1.32%, T1: 1.17%, T2: 1.57%, T3: 1.33%.